Issues and Challenges Faced by SME’s in Sultanate of Oman during COVID-19: A Case Study of the Tourism Sector - Alhanai, Yasser; Matriano, Dr. Maria Teresa (Advances in Social Sciences Research Journal, 2021)
The world economy has been greatly affected by Covid-19 and Oman has been among the countries facing challenges in the operation of SMEs in handling of business needs and meeting regular fixed costs. The SMEs most affected are those in the tourism sector where travel restrictions and lockdowns could not allow the businesses to receive visitors as expected who are the customers to the services and products offered. Using the sample size of 187 participants who own or work at the SMEs in tourism sector, it was established that the applied legislations and restrictions of movement had a positive correlation to SMEs business operations with a positive correlation coefficient of 0.478. However, a recommendation to the issues and challenges were issued stating that SMEs should invest in technology & tools, creation of an oversight of SME financial status, prioritising of value over culture, and trusting & empowering the people that deal with SMEs.